2018
DOI: 10.1177/0046958018759421
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Hearing Loss in Older Adults: Results of a Survey Conducted in 500 Subjects Across 5 European Countries as a Basis for an Online Awareness Campaign

Abstract: The objectives of this study were to assess the factors which contribute to individuals’ health motivation to address hearing loss and to gather baseline data that could then be used to measure the impact of an awareness campaign. An online questionnaire with 13 closed set questions was completed by 100 subjects in each country including Austria, Germany, France, Sweden, and the United Kingdom. The questionnaire was based around the Health Belief Model, which describes how, in order to take action to address a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 16 publications
0
30
0
2
Order By: Relevance
“…The same questionnaire with 13 closed set questions as described in D'Haese et al 7 was used to collect data which was compared with baseline data collected from June 1, 2013 to July 31, 2013, prior to any advertising and reported by D'Haese et al 7 No ethics approval was required for the study as it was designed to investigate the health issues within a population in order to improve population health and there was no intervention. It was conducted according to the principles laid out in the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The same questionnaire with 13 closed set questions as described in D'Haese et al 7 was used to collect data which was compared with baseline data collected from June 1, 2013 to July 31, 2013, prior to any advertising and reported by D'Haese et al 7 No ethics approval was required for the study as it was designed to investigate the health issues within a population in order to improve population health and there was no intervention. It was conducted according to the principles laid out in the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…6 There is a lack of awareness of CIs in both professionals and potential recipients. 7,8 In order to come forward to be assessed for a CI, individuals must feel that their hearing loss is severe and is affecting their quality of life. 9 However, the benefits of the treatment must outweigh the risks and barriers to receiving it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the resulting data, good hearing was regarded as being important in all countries and when motivated to do so, people sought information from medical professionals, mostly GPs and ENT specialists, about their hearing problems [48]. There was agreement that the main sign of hearing loss was turning up the TV or radio.…”
Section: Raising Awarenessmentioning
confidence: 99%
“…Although many studies have confirmed significant improvement in speech understanding after cochlear implantation, even in aging patients, many potential adult CI candidates are unaware of this treatment option or opt out, with <10% of those with severe-to-profound bilateral sensorineural hearing loss receiving a cochlear implant (14). This low rate is widespread, regardless of geographical location, and is independent of how health services are organized and countryspecific economic output (15)(16)(17)(18). In contrast, congenital severeto-profound sensorineural hearing loss is identified at a very young age using universal neonatal hearing screening and the cochlear implantation rate in children is high (19).…”
Section: Rehabilitation Of Hearing Lossmentioning
confidence: 99%